Increasing relative prevalence of HSV-2 infection among men with genital ulcers from a mining community in South Africa. Issue 3 (1st June 2003) - Lai, W; Chen, C Y; Morse, S A; Htun, Ye; Fehler, H G; Liu, H; Ballard, R C
Abstract : Objectives: To determine the aetiology of genital ulcer disease (GUD) and its association with HIV infection in the mining community of Carletonville, South Africa, from two cross sectional surveys of consecutive men presenting with genital lesions during October 1993 to January 1994 and July to November 1998. Methods: A multiplex polymerase chain reaction (M-PCR) assay combined with amplicon detection was used to identify DNA specific sequences of Treponema pallidum, herpes simplex virus (HSV), and Haemophilus ducreyi . A real time PCR assay was used to differentiate between HSV-1 and HSV-2. Results: M-PCR detected T pallidum, HSV, and H ducreyi in 10.3%, 17.2%, and 69.4% of 232 GUD patients during 1993–4 and in 12.4%, 36.0%, and 50.5% of 186 GUD patients in 1998. The proportion of patients with more than one agent increased significantly from 7.3% (17/232) in 1993–4 to 16.7% (31/186) in 1998 (p <0.01). HSV-2 was detected in a higher proportion of ulcer specimens from HIV infected patients than in specimens from HIV uninfected patients during both time periods (1993–4: 26.2% v 6.7%, p <0.001; 1998: 42.1% v 29.6%, p >0.09). Conclusions: Based on two cross sectional surveys, 4 years apart, chancroid remained the leading cause of GUD in men who presented at the STD clinic with genital ulcers in the mining community of Carletonville, South Africa. The relative prevalence of primary syphilis has remained low. However, HSV-2 has emerged as a more significant cause of GUD and the proportion of GUD patients infected with more than one agent also increased significantly. HSV-2 DNA was detected in a significantly higher proportion of ulcer specimens from HIV positive patients than from HIV negative patients. No association was found between HIV infection status and the relative prevalence of chancroid or syphilis.